2015
DOI: 10.1371/journal.ppat.1004930
|View full text |Cite
|
Sign up to set email alerts
|

Potent Cell-Intrinsic Immune Responses in Dendritic Cells Facilitate HIV-1-Specific T Cell Immunity in HIV-1 Elite Controllers

Abstract: The majority of HIV-1 elite controllers (EC) restrict HIV-1 replication through highly functional HIV-1-specific T cell responses, but mechanisms supporting the evolution of effective HIV-1-specific T cell immunity in these patients remain undefined. Cytosolic immune recognition of HIV-1 in conventional dendritic cells (cDC) can facilitate priming and expansion of HIV-1-specific T cells; however, HIV-1 seems to be able to avoid intracellular immune recognition in cDCs in most infected individuals. Here, we sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
85
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 70 publications
3
85
0
Order By: Relevance
“…Previous studies with peripheral blood myeloid MDDCs and MDDCs from HIV-1 elite controllers have shown that these cells may be critical for viral control, acting to capture the virus and enhance T cell-specific immunity to HIV-1 while being less susceptible to HIV-1 infection than MDDCs from healthy controls (108,109). Understanding the mechanisms that control HIV-1 replication in MDDCs, which are overcome by Vpr, might lead to new insights into viral dissemination and persistence in vivo and the development of novel anti-HIV-1 therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies with peripheral blood myeloid MDDCs and MDDCs from HIV-1 elite controllers have shown that these cells may be critical for viral control, acting to capture the virus and enhance T cell-specific immunity to HIV-1 while being less susceptible to HIV-1 infection than MDDCs from healthy controls (108,109). Understanding the mechanisms that control HIV-1 replication in MDDCs, which are overcome by Vpr, might lead to new insights into viral dissemination and persistence in vivo and the development of novel anti-HIV-1 therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…While suppression of mDC-mediated stimulation of IFN-γ release from CD4 T cells was not statistically significant, addition of IL-12 strongly enhanced the capacity for mDC to drive cytokine production from T cells. Increased recruitment of mDC to lymphoid tissues is associated with disease progression in SIV-infected macaques (27), and in HIV infection, mDC from the blood of elite controllers but not individuals with chronic progressive infection stimulate CD4 T cell proliferation and IFN-γ release from HIV-specific CTL (17). Collectively these data are suggestive of a generalized defect in mDC T cell-stimulating function in HIV and SIV infection that reduces immune control of virus thereby promoting disease development.…”
Section: Discussionmentioning
confidence: 99%
“…Many groups have examined the impact of HIV and SIV infection on production of pro-inflammatory cytokines by isolated DC and macrophages (3, 915) as well as the effect of HIV exposure in vitro on the IFN response (16). However, studies exploring the T-cell stimulating function of myeloid DC (mDC) and plasmacytoid DC (pDC) in HIV or SIV infection have been limited (11, 13, 14, 17), and virtually nothing is known about the APC function of macrophages in these infections.…”
Section: Introductionmentioning
confidence: 99%
“…Here, we used HIV-1 controllers, a group of patients widely used for investigation of HIV-1 immune defense mechanisms in previous studies (43)(44)(45) DCs in HIV-1 controllers seem to have a distinct functional and phenotypic profile that can contribute to the induction of highly functional HIV-1-specific T cell responses. These abilities have been associated with an altered expression profile of immunoregulatory receptors (46) and with enhanced abilities for HIV sensing and innate immune recognition (47). However, the impact of DCs from these patients on Tfh development is still unclear, and investigations of DCs on induction of Tfh have mostly been limited to animal studies (11,48,49) or experiments with in vitro generated monocyte-derived DCs (MDDCs) (25,33), rather than primary DCs.…”
Section: Cxcr3mentioning
confidence: 99%